Risk Factors of Chylothorax After Congenital Heart Surgery in Infants: A Single-Centre Retrospective Study - Zhang RG; Liu YM; Yao ZY; Fang JX; Li Y; Zheng ML; Sun X; Wen SS; Wang XM; Zhuang J; Luo DD; He SR (Dove Medical Press, 2024)
Rui-Gui Zhang,1- 3 Yu-Mei Liu,2- 4 Zhi-Ye Yao,2,3 Jing-Xuan Fang,4 Yuan Li,2- 4 Man-Li Zheng,2,3 Xin Sun,2,3 Shu-Sheng Wen,4,5 Xi-Meng Wang,4,6 Jian Zhuang,4 Dan-Dong Luo,4 Shao-Ru He1- 3 1The Second School of Clinical Medicine, Southern Medical University, Guangzhou, 510260, People's Republic of China; 2Department of Neonatal Pediatrics, Guangdong Provincial People's Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, 510080, People's Republic of China; 3Department of Pediatrics, Guangdong Provincial People's Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, 510080, People's Republic of China; 4Guangdong Cardiovascular Institute, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangzhou, 510080, People's Republic of China; 5Department of Cardiovascular Surgery, Guangdong Cardiovascular Institute, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangzhou, 510080, People's Republic of China; 6Global Health Research Center, Guangdong Provincial People's Hospital, Guangdong Academy of Medical Sciences, Guangzhou, 510080, People's Republic of ChinaCorrespondence: Shao-Ru He, Department of NICU, Guangdong Provincial People's Hospital (Guangdong Academy of Medical Sciences, No. 106 of Zhongshan 2nd Road, Yuexiu District, Guangzhou, 510080, People's Republic of China, Tel +8620-83827812, Email Hshru_rsh@163.comBackground: Studies of chylothorax after congenital heart disease in infants are rare. Chylothorax has a higher incidence in infancy, but its risk factors are not well understood.Objective: The purpose of this study is to investigate the risk factors of chylothorax after congenital heart surgery in infants.Methods: This retrospective study included 176 infants who underwent congenital heart disease surgery at the Guangdong Cardiovascular Institute, China, between 2016 and 2020. According to the occurrence of chylothorax, the patients were divided into a control group (n = 88) and a case group (n = 88). Univariate and multivariate logistic regression were performed to analyse the incidence and influencing factors of chylothorax after congenital heart surgery in infants.Results: Between 2016 and 2020, the annual incidence rate fluctuated between 1.55% and 3.17%, and the total incidence of chylothorax was 2.02%. Multivariate logistic regression analysis showed that postoperative albumin (p = 0.041; odds ratio [OR] = 0.095), preoperative mechanical ventilation (p = 0.001; OR = 1.053) and preterm birth (p = 0.002; OR = 5.783) were risk factors for postoperative chylothorax in infants with congenital heart disease.Conclusion: The total incidence of chylothorax was 2.02% and the annual incidence rate fluctuated between 1.55% and 3.17% between 2016 and 2020. Premature infants, longer preoperative mechanical ventilation and lower albumin after congenital heart surgery may be risk factors for chylothorax. In addition, infants with chylothorax are inclined to be infected, need more respiratory support, use a chest drainage tube for longer and remain longer in hospital.Keywords: congenital heart surgery, congenital heart disease, postoperative chylothorax, infant, risk factor